2003
DOI: 10.1002/art.10771
|View full text |Cite
|
Sign up to set email alerts
|

Valine/valine genotype at position 247 of the β2‐glycoprotein I gene in Mexican patients with primary antiphospholipid syndrome: Association with anti–β2‐glycoprotein I antibodies

Abstract: Objective. To determine the polymorphism at position 247 of the ␤ 2 -glycoprotein I (␤ 2 GPI) gene in Mexican patients with antiphospholipid syndrome (APS) and to compare these data in patients with or without antibodies to ␤ 2 GPI and with the clinical manifestations of APS.Methods. We studied 39 patients with primary APS and compared them with 106 clinically healthy subjects. Polymorphism was determined by polymerase chain reaction-restriction fragment length polymorphism. The presence of "true" anticardioli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 15 publications
(30 reference statements)
5
41
0
3
Order By: Relevance
“…PCR products were separated on a 2% agarose gel. Enzyme digestion was performed with I (for Val247Leu; New England Biolabs, Spain) and BstB I (for Trp316Ser) (New England Biolabs, Spain), as previously described [12].…”
Section: Molecular Analysis Of B2gpi Gene Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR products were separated on a 2% agarose gel. Enzyme digestion was performed with I (for Val247Leu; New England Biolabs, Spain) and BstB I (for Trp316Ser) (New England Biolabs, Spain), as previously described [12].…”
Section: Molecular Analysis Of B2gpi Gene Polymorphismsmentioning
confidence: 99%
“…While studies in Asian [7,11] and American Hispanic [12][13][14] populations have identified clinical and serological associations between APS and b2GPI gene polymorphisms, other studies, mainly in Caucasian populations, have found no such relationship [7,[15][16][17]. The current study evaluated the presence of polymorphisms Val247Leu and Trp316Ser in a Spanish population of APS patients and healthy controls and the possible correlation with the development of anti-b2GPI antibodies and other aPL and associated clinical manifestations.…”
Section: Introductionmentioning
confidence: 97%
“…22 A troca do aminoácido Leu pela Val (códon 247), no V domínio da β 2 GP1, pode ocasionar modificação estrutural na proteína, ocasionando a produção de anticorpos antiβ 2 GP1, presentes na SAF, 23 e os indivíduos que apresentam homozigose Val247Val possuem maior risco de desenvolver SAF. 24,25 Neste estudo avaliou-se o polimorfismo genéti-co, localizado no códon 247 do exon 7 do gene da β 2 GP1 em amostra populacional brasileira composta por indivíduos hansênicos e saudáveis. Houve maior prevalência do genótipo Val/Val no grupo de hansêni-cos, em relação à do grupo controle.…”
Section: Discussionunclassified
“…Todos os pacientes MB com FTE apresentaram heterozigose ou homozigose (Val/Val), corroborando estudos que atribuem FTE e SAF ao polimorfismo Val247Leu. 13,24,25 Alguns estudos têm relacionado a presença desse polimorfismo com AAF em pacientes com SAF, porém os resultados são controversos. Paloma et al [24][25][26][27] Na hanseníase MB, há descrição da presença de AAF, porém a ocorrência da associação com SAF é rara.…”
Section: Discussionunclassified
See 1 more Smart Citation